Good practices for the marketing of food ready for consumption in public markets in Recife-PE (Research, Society and Development, 2021)
In recent years, concern for food security has been growing in the population due to the increase in foodborne diseases. Considering that traders in public markets routinely provide food to the population, it is necessary to seek means to ensure their access to information, ensuring effective intervention in the risks inherent to the consumption of low hygienic and sanitary quality foods. The objective of this study was to evaluate the hygienic and sanitary conditions for the commercialization of food in public markets in Recife - PE. This is an exploratory, descriptive study with quantitative approach, carried out in the main public markets of the city of Recife - PE, which met the eligibility criteria, being the sampling of the intentional type. Municipal Markets that sell food ready for human consumption were included; physical commercial establishments; located in the City of Recife. The sample was composed of food merchants from the 15 public markets of Recife-PE. It was observed that 65.4% of the participants in the study were female, with the age group between 18 and 60 years, it was also observed that 49% of the participants attended high school. It was observed that in 53.3% of the physical commercial establishments (boxes or stores) analyzed, the handlers used drinking water, a low percentage since water and an indispensable item for all stages of food preparation. Most merchants do not follow hygienic and sanitary standards which generates the compromise of the quality of the food that will be consumed.